INTEGRATION OF DIGITAL STORYTELLING IN WRITING INSTRUCTION TO ENHANCE STUDENTS’ CREATIVITY AND LITERACY PROFICIENCY: A CASE STUDY - Nirwanto Maruf; Khoirul Anwar; Salsabilah Latifa (Indonesian EFL Journal, 2025)
This study investigated the effectiveness of integrating digital storytelling platforms in foreign language writing instruction to enhance students’ creativity and literacy proficiency, focusing on grammar accuracy, vocabulary usage, narrative structure, and creativity. Conducted at an Indonesian secondary school, the research employed a mixed-methods one-group pretest-posttest design involving 60 eleventh-grade students. Quantitative analysis revealed significant improvements across all measured writing dimensions: grammar accuracy improved significantly (t(29) = 7.85, p < .001), vocabulary usage showed marked gains (t(29) = 6.97, p < .001), narrative structure increased substantially (t(29) = 8.21, p < .001), and creativity scores rose notably (t(29) = 7.35, p < .001). Complementary qualitative data from classroom observations and semi-structured interviews highlighted increased student motivation, strategic cognitive engagement, and active participation throughout the intervention. Findings suggest that digital storytelling fosters a rich multimodal learning environment that simultaneously supports technical writing accuracy and creative expression. The scaffolded instructional design—including storyboarding, multimedia integration, and peer feedback—enabled learners to organize coherent narratives, enhance vocabulary, and refine grammatical skills. Participants also reported heightened enthusiasm and metacognitive awareness, indicating deeper involvement in the writing process. These results align with contemporary theories advocating multimodal and technology-enhanced pedagogies in language education. Despite limitations including sample size and design constraints, the study offers valuable empirical evidence from an underexplored Indonesian EFL context and supports the adoption of digital storytelling as an engaging, holistic strategy to improve foreign language writing and foster essential 21st-century skills such as creativity and critical thinking.